2015
DOI: 10.1016/j.sleh.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Tailored lighting intervention for persons with dementia and caregivers living at home

Abstract: Objectives Light therapy has shown promise as a nonpharmacological treatment to help regulate abnormal sleep-wake patterns and associated behavioral issues prevalent among individuals diagnosed with Alzheimer’s disease and related dementia (ADRD). The present study investigated the effectiveness of a lighting intervention designed to increase circadian stimulation during the day using light sources that have high short-wavelength content and high light output. Methods Thirty-five persons with ADRD and 34 car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(121 citation statements)
references
References 41 publications
5
115
1
Order By: Relevance
“…Since the SCN of patients with severe AD is likely to be more degenerated, and the circadian activity rhythms deteriorate as the disease progresses, it is still possible that patients with mild or moderate AD would benefit from light treatment more than those with severe AD. For example, Figueiro et al [37] treated a group of 35 patients with mild or moderate dementia for 4 weeks with a tailored lighting intervention and, differently from previous studies, they showed a significant reduction of depressive symptoms. Barrick et al [56] showed that ambient bright light is not effective in reducing agitation in institutionalized persons with dementia and may exacerbate this behavioral symptom in severely demented patients.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Since the SCN of patients with severe AD is likely to be more degenerated, and the circadian activity rhythms deteriorate as the disease progresses, it is still possible that patients with mild or moderate AD would benefit from light treatment more than those with severe AD. For example, Figueiro et al [37] treated a group of 35 patients with mild or moderate dementia for 4 weeks with a tailored lighting intervention and, differently from previous studies, they showed a significant reduction of depressive symptoms. Barrick et al [56] showed that ambient bright light is not effective in reducing agitation in institutionalized persons with dementia and may exacerbate this behavioral symptom in severely demented patients.…”
Section: Resultsmentioning
confidence: 98%
“…Figueiro et al [36, 37] also obtained an improvement in sleep parameters (e.g., increased total sleep time and sleep efficiency) using a tailored lighting intervention with bright light, from 6 or 8 am to 6 pm, in a group of patients diagnosed with AD and related dementia; however, these authors did not show any effect on the IS and IV parameters. Similar results were also found by Sloane et al [38] who, after a tailored lighting intervention, did not find any significant changes in the actigraph measures (i.e., IS and IV scores); light stimulation levels achieved in this study seem to have some effect on sleep pattern, albeit minor and not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because brightlight therapy in an ADRD population significantly improves night time sleep [17] and reduces cognitive decline [25]. Furthermore, pain is strongly linked to depression, and either condition can be cause or effect of the other [19].…”
Section: Future Workmentioning
confidence: 99%